2016
DOI: 10.1016/j.bpsc.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Imaging of White Matter in Schizophrenia: Progress and Future Directions

Abstract: Diffusion tensor imaging (DTI) is a powerful tool for the in-vivo assessment of white matter microstructure. The application of DTI methodologies to the study of schizophrenia has supported and advanced the hypothesis of schizophrenia as a disorder of disrupted connectivity. In the context of impaired structural connectivity, the extended time frame of white matter development may offer unique opportunities for treatment that can capitalize on the neural flexibility that is still present in the period leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 146 publications
3
30
0
Order By: Relevance
“…There are several potential explanations for our negative findings. One possibility, is that schizophrenia is characterized by altered white matter pathways (Ellison-Wright and Bullmore, 2009; Karlsgodt, 2016), which may be accounting for the observed impairment in cognitive empathy in schizophrenia. Thus, Diffusion Tensor Imaging (DTI, e.g., fiber tractography) could be one possible tool to measure the complex integration of networks supporting cognitive empathy.…”
Section: Discussionmentioning
confidence: 99%
“…There are several potential explanations for our negative findings. One possibility, is that schizophrenia is characterized by altered white matter pathways (Ellison-Wright and Bullmore, 2009; Karlsgodt, 2016), which may be accounting for the observed impairment in cognitive empathy in schizophrenia. Thus, Diffusion Tensor Imaging (DTI, e.g., fiber tractography) could be one possible tool to measure the complex integration of networks supporting cognitive empathy.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of cannabis on white matter volume in schizophrenia is weak 69,70 but DTI studies have shown both FA increases and decreases in cannabis-using patients with schizophrenia compared to non-using patients 28,71 . Previous analyses on the present study sample have demonstrated that familial predisposition for psychotic disorder is associated with greater cannabis-induced reduction in cortical thickness 72 . The current DTI results suggest that there is no marked effect of cannabis on microstructural white matter, as the controlling TBSS analyses for cannabis use did not change the results.…”
Section: Environmental Factorsmentioning
confidence: 73%
“…Secondary measures as radial diffusivity for the degree of myelination and axial diffusivity for axonal organization are more informative on the etiology of WM alterations in terms of myelin loss or axonal incoherence but as yet, less frequently reported. Lately, as it is apparent that the structure of neural tissue may be too complex to comprehend through a single diffusion tensor, the focus has shifted to more advanced WM measures derived from 'Free Water Imaging (FWI)' and the 'Permeability Diffusivity Index (PDI) 72 . Future studies examining WM integrity should implement these new diffusion methods to investigate the nature of the alterations in WM microstructure in more detail.…”
Section: Dti Measurementioning
confidence: 99%
See 2 more Smart Citations